Preserving The Environment and Rural Community in Sabah Through the Empowerment of Gravity-Flow Water Systems: A Survey Based on APPGM-SDG Solution Projects - Jafar, Adi; Mohamad Ridzuan, Mohammad Ikhram; Joko, Eko Prayitno; Dollah, Ramli; Madli, Faerozh (Journal of Technical Education and Training, 2025)
The gradual increase in the world’s population has caused the demand for domestic water resources to rise as well. In certain situations, existing water treatment plants cannot cope with the high demand of residents. Hence, to avoid a water supply crisis, the community should not entirely rely on one type of water supply (treated tap water supply). Instead, there should be an alternative water supply source in preparation for overcoming a potential water supply crisis. The gravity-flow water system is an efficient technique that has long been implemented in the rural communities of Sabah. Accordingly, this research examines the suitability of the gravity-flow water system implemented in rural areas by focusing on its advantages in preserving the environment and community. Raw data in the form of site visits (SV), focus group discussions (FGD), project proposals, monthly reports and the final report obtained from APPGM-SDG Solution Projects are used to achieve the objective. The study results revealed that the villagers’ implementation of the gravity-flow water system in several rural areas in Sabah (Kg. Sayap, Kg. Bakuku & Kg. Tanobon Baru) can preserve the environment by sustaining rivers and river basins. Apart from that, the implementation of gravity-flow water systems can also reduce the economic burden of villagers who, on average, have a low economic status. Indirectly through this study also found that there is a great need for technical skills and vocational training (TVET). By empowering TVET indirectly, there is potential for the development of gravity water systems, especially in terms of ideal design.